TENS to the Lateral Aspect of the Knees During Stance Attenuates Postural Sway in Young Adults. (2007) - Laufer, Yocheved; Dickstein, Ruth
Abstract : Somatosensory input is known to be essential for postural control. The present study examined the effects on postural sway of sensory input delivered via transcutaneous electrical nerve stimulation (TENS) applied to the knees during stance. Electrodes from a dual-channel portable TENS unit were adhered to the skin overlying the lateral and medial aspect of both knees of 20 young healthy volunteers (mean age 24.0 years, standard deviation 4.0). Postural sway parameters were obtained during static bipedal stance with an AMTI force platform. Four stimulation conditions were tested with eyes open and with eyes closed: no TENS; TENS applied bilaterally; and TENS applied to either the right or the left knee. Participants underwent two eight-trial blocks, with each trial lasting 30 seconds. The order of conditions was randomized for each participant. Stimulation consisted of a biphasic symmetrical stimulus delivered at the sensory detection level, with a pulse duration of 200μsec and a pulse frequency of 100Hz. The application of TENS induced significant reductions in mean sway velocity and in the medio-lateral dispersion of the center of pressure, with no corresponding effect on the anterior-posterior dispersion. These findings suggest that electrical stimulation delivered at the sensory detection level to the lateral aspects of the knees may be effective in improving balance control, and that this effect may be directionally specific.